The Effect of Motivation, Work Ethos and Work Discipline on Teacher Work Productivity at Madrasah Ibtidaiyah Negeri (MIN) Binjai - Syafriadi Syafriadi; Sutaryat Trisnamansyah; Husen Saeful Insan; Waska Warta (International Journal of Nusantara Islam, 2021)
Madrasah Ibtidaiyah (MI) is the most basic level educational institution which is a continuation of the Raudhatul Athfal (RA) or Kindergarten (TK) level in formal education in Indonesia, which is managed by the Ministry of Religion. The problem is whether partially and simultaneously Motivation, Work Ethic and Work Discipline on Teacher Work Productivity. The technique in the research was carried out by means of a questionnaire by distributing a list of questions to respondents as many as 40 teachers. The research shows that the Fcount value is 544.007 with a significant level of 0.00. Because Fcount 544.007> Ftable 2.87 and the significant probability is much smaller than 0.05, namely 0.00 t table 1.688 with a significant 0.046 < 0.05, meaning that partially there is a positive and significant effect of Work Motivation on Work Productivity. The results of the work ethic variable test, the value of tcount -3.848 < t table 1.688 with a significant 0.000> 0.05, meaning that it is partially influential but not significant on work ethics on work productivity. The result of the work discipline variable test, tcount 4,912 > t table 1,688 with a significant 0,000 > 0.05, meaning that partially there is a positive and significant influence of Work Discipline on Work Productivity. While the adjusted R square is 0.977, this means that 97.8% of the variation in Work Productivity can be explained by the independent variable Work Motivation, Work Ethic, Work Discipline, while the rest (100% - 97.7% = 2.3%) can be explained by other independent variables.